PREDICATE EXTENDERS WITH THE SEMANTICS OF THE MANNER OF ACTION AS OBLIGATORY PARTS OF A SENTENCE - Степаненко, Микола (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
With the linguistic doctrine of the minimal and extended sentence schemes as the theoretical background, the valency potential of the predicate verbs which are characterised by the identification semes «attitude» (to treat /to have treated, to approach, to behave with, to deal with [with someone], to accept) and «behaviour» (behave, hold, do, treat) is revealed. The object of the study is syntactic constructions with the obligatory predicate extender that possesses the semantics of the manner of action and corresponds to the adverbial modifier of the manner of action on the formal grammatical level. The purpose of the article is to find out the interaction of formal-grammatical and semantic valency in the structure of sentences with right-hand distributors which demonstrate the value of the manner of action. Results. It is proved that the distinguished basic valency carriers are informatively insufficient. They require the obligatory filling of the syntactic positions programmed by them with the morphological forms that are not strictly determined but have the strictly regulated meaning which can be subjected to internal semantic differentiation. This meaning is defined as the meaning of the manner of action or the meaning of simultaneously expressed the manner of action and the object of action. In particular, the semantic specification of each of the predicate verbs is analysed, as well as conditions for their obligatory inclusion into the sentences built upon the structural models Sub + Praed + Adv qual and Sub + Praed + Obj + Adv qual are discussed. The possible types of predicate extenders (descriptive adverbs, adverbs with the comparative meaning, phraseologized compounds that correlate semantically with attributive adverbs, prepositional forms, subordinate sentences with the meaning of the manner of action and the quality of action) are described in detail. The typology of meanings of these predicate extenders is developed, and peculiarities of their formal grammatical organization are characterized. Besides, the effect of the principle of the lexical-semantic selectivity on the level of the valency frame «predicate verb + predicate extender with the meaning of the manner of action or manner of action and the object of action» is disclosed. Furthermore, the degree of productivity of predicate verbs and, consequently, the degree of productivity of the sentences which they constitute is found out. Originality. The analysed sentences are interpreted as a multi-level syntactical unit, the formalgrammatical and semantic-syntactic tiers of which are in symmetric-asymmetric determinative relationships. Conclusion. It is proved that predicate extenders of the manner of action and the object of action that perform the function of the obligatory components help to transfer the predicate verbs from the sphere of relative informative insufficiency into the sphere of semantic self-sufficiency which results in making the content of the sentences based on the structural models Sub + Praed + Adv qual and Sub + Praed + Obj + Adv qual semantically appropriate